Rainwater harvesting practices and resource conservation in agroforestry system in red soils of Bundelkhand - Narayan, Dev; Kumar, Prabhat; Kumar, Manish; Yadav, R.S. (Indian Journal of Agroforestry, 2020)
A field study was conducted to evolve a suitable in-situ rainwater harvesting practice for resource conservation and augmenting growth of aonla in agroforestry system on sloping lands in red soils of Bundelkhand region. The treatments (farmer's practice of aonla planting with 0.027 m3 pit (control), pit filled up to 0.75 m with 1 m3 pit, crescent shaped micro- catchment with 1 m3 pit and V-shaped micro-catchment with 1 m3 pit) were laid out in RBD in four replications in runoff plots of 21 m Ã— 14 m at 2% slope. In inter-spaces, black gram - Indian mustard crop sequence was practiced. Results showed that highest runoff (38.9%), soil loss (3.79 tha-1) and nutrient loss (Organic carbon, N, P and K), lower grain yield in black gram (221 kg ha-1) and Indian mustard (1082 kg ha-1) and low growth of aonla (height 1.83 m and girth 1.3 cm) were recorded under farmer's practice. However, lowest runoff (23.3%), soil loss (1.97 tha-1) and nutrient loss, higher grain yield of black gram (334 kg ha-1) and Indian mustard (1580 kg ha-1) and higher growth of aonla (height 2.21 m and girth 1.5 cm) were obtained under Vshaped micro-catchment. Based on the present findings, V-shaped micro-catchment could be a suitable in-situ rainwater conservation practice for resource conservation and enhancing yield of intercrops and growth of aonla under aonla-based agroforestry system on sloping lands in red soils of Bundelkhand region.